THE ROLE OF OUTSOURCING SERVICES IN THE DIGITAL ECONOMY IN UZBEKISTAN - Saatova Lolakhon Ergashevna; Rayimov Azamjon Ruzievich (Scholar Express Journals, 2023)
In this paper the role of outsourcing services in the digital economy in Uzbekistan is discussed. Moreover, reviews on the type of service provided by the outsourcing company, its advantages, and disadvantages, there is a high demand for several services in addition to the outsourcing service are given.
Keywords: Employee; freelance; outsourcing